ECONOMIC REFORMS IN KARAKALPAKSTAN DURING THE TRANSITION TO A MARKET ECONOMY - Saribaev, Aziz Ktaybekovich; Jiyenbaeva, Biybimaryam Jalgasbaevna (SCIENCE and SOCIETY, 2026)
The article examines the characteristics of economic reforms implemented in Karakalpakstan during the transition to a market economy in 1991–2000. The main directions of transformations related to the formation of market relations, the privatization of state property, the reform of the economic sector, the development of entrepreneurship and small business, and structural changes in the regional economy are analyzed.